An Alternative and Complementary Approach to Interpreting the Regression on the Dependent Latent Variable in a MIMIC Model - Vázquez Peña, Fernando R.; Grande Ratti, María F.; Cordón Pozo, Eulogio (Revista del Hospital Italiano de Buenos Aires, 2025)
Letter to the Editor regarding the article by Grande Ratti et al., entitled “MIMIC Models: From Neuroscience to the Health Sciences,” which proposes a novel and complementary approach to the interpretation of MIMIC models, based on the analysis of estimated (rather than standardized) coefficients.
Keywords: letter; MIMIC model; alternative interpretation